KERASULAN AWAM DI BIDANG POLITIK (SOSIAL-KEMASYARAKATAN), DAN RELEVANSINYA BAGI MULTIKULTURALISME INDONESIA - Agustinus Wisnu Dewantara (Lembaga Penelitian STKIP Widya Yuwana, 2017)
The political responsibility is important, not because of the need for the love of the homeland and the challenge of the disintegration of the nation in multicultural sphere, but must be born of deep Christian faith. This paper specifically addresses to the lay apostolate in socio-politics-society. The Catholic laity was also called to be salt and light in the political world. The emergence of some form of practical theology (such as liberation theology and political theology) affirms that concern. The theme of the laity will be juxtaposed with a review of the